Beyond "Meat Free Monday": A mixed method study of giving up eating meat. (1st November 2021) - de Visser, Richard O.; Barnard, Suzanne; Benham, Daniel; Morse, Rachel
Abstract: Increasing numbers of people are vegan, vegetarian, or reducing meat consumption. There has also been growth in campaigns such as Meat Free Monday (MFM) that encourage and support reduced meat consumption. We conducted a mixed-method exploration of the behaviour and beliefs associated with reducing or eliminating meat consumption. An online questionnaire was completed by an opportunistic sample of 655 people aged 18–82 who were registered on the MFM website, and were meat eaters at the time of registering. The key focus of quantitative analyses was comparisons between three groups: those who described themselves as "omnivores" who ate all meat at the time of completing the survey, those who ate only some meat, and those who had stopped eating meat since registering for MFM. The qualitative component entailed Interpretative Phenomenological Analysis of in-depth interviews with 18 people who had completed the questionnaire. The quantitative data revealed that people who had stopped eating meat since engaging with the MFM campaign had more positive attitudes toward being vegetarian or vegan, had been engaged with MFM for a longer time, and had used more elements of the MFM website. The qualitative data illustrated that individuals understood and appreciated MFM's aim of supporting people to make an initial change and then considering expanding on this. Interviewees highlighted the value and importance of campaign materials that helped them to turn their beliefs and motivation into enduring behaviour change. The observed associations between longer engagement with the campaign and greater behaviour change suggest that MFM and similar campaigns will maximise their impact if they can maintain people's active engagement: that this will necessitate deeper understanding of the forms of support and advice are most wanted and most effective.